Study on the properties of palm oil fiber - El-Gelany Ismail, Mohamed Abdelkader (Faculty of Civil Engineering, 2009)
This study investigated the strength and durability of Palm Oil Fiber Reinforced Concrete (POFRC). Two POFRC mixes with two different content and length of palm oil fiber (POF) were used. Specimen PF1 contained 0.50% POF of 3 cm length while specimen PF2 contained 0.25% POF of 5 cm length. The strength and durability of both specimens were compared with a control mix, P0. The concrete specimens were cured in water for 28 days, before immersing them in 1% hydrochloric acid solution for 1800 hours. The durability of POFRC against acid attack was evaluated by the loss of weight and compressive strength. In this paper, the attack of chloride ions on specimens immersed in 3% sodium chloride solution using the colorimetric method was studied. After 7, 28 and 90 days curing, the progressive deterioration was evaluated through spraying of 0.2N silver nitrate solution on the split cylinders and by visual inspection. Microanalyses were conducted upon test termination to elucidate the damage mechanisms using FESEM and EDX analysis. In most cases, PF1, which had the highest fiber content (0.5%) did not give good results while PF2 showed good performance against deteriorations compared to the control mix, P0.